Emergency airway training: "Who are you going to FONA?". (17th September 2020) - Bhalla, Sanjana; Beegun, Issa; Hogan, Chris; Awad, Zaid; Tolley, Neil
Abstract: Objectives: To demonstrate face and content validity of a home‐made simulation model as a training tool for front of neck access (FONA) procedures. Design: This was a prospective evaluation study, in which experienced otolaryngologists and trainees were recruited to complete 3 tasks using our FONA model. Setting: The study was completed during regular simulation training days and international conferences. Participants: A total of 52 participants completed the questionnaire and were included in the study; 25 were experts and 27 were trainees. Main outcome measures: All participants completed a validated 15‐item questionnaire using a 5‐point likert scale to assess the model across 4 domains: face validity (FV), global content (GC), task‐specific content (TSC) and curriculum applicability (CTR). Results: There were no statistically significant differences between the groups ratings for FV, GC, TSC or CTR ( P = .76, .13, .4 and .67, respectively). The model achieved a median FV of 4 (IQR 4‐5) with the agreement of experienced and trainee groups (68.9% and 92%, respectively). The median GC validity score was 5 (IQR 4‐5) with the agreement of 87.6% and 98.4% in respected groups. The model achieved a median TSC of 4.8 (IQR 4‐5) with the agreement of 54.5% and 99% in respected groups. The median CTR score was 5 (IQR 4‐5) with the agreement of 54.4% and 100% in respected groups. Conclusion: Our home‐made FONA model achieved face and content validity for training and is safe and affordable for teaching basic front of neck access skills to otolaryngology trainees.